Swimming strategy and body plan of the world's largest fish: implications for foraging efficiency and thermoregulation - Meekan, Mark; Fuiman, Lee; Davis, Randall; Berger, Yuval; Thums, Michele (Frontiers in Marine Science, 2015)
The largest animals in the oceans eat prey that are orders of magnitude smaller than themselves, implying strong selection for cost-effective foraging to meet their energy demands. Whale sharks (Rhincodon typus) may be especially challenged by warm seas that elevate their metabolism and contain sparse prey resources. Using a combination of biologging and satellite tagging, we show that whale sharks use four strategies to save energy and improve foraging efficiency: (1) fixed, low power swimming, (2) constant low speed swimming, (3) gliding, and (4) asymmetrical diving. These strategies increase foraging efficiency by 22–32% relative to swimming horizontally and resolve the energy-budget paradox of whale sharks. However, sharks in the open ocean must access food resources that reside in relatively cold waters (up to 20°C cooler than the surface) at depths of 250–500 m during the daytime, where long, slow gliding descents, continuous ram ventilation of the gills and filter-feeding could rapidly cool the circulating blood and body tissues. We suggest that whale sharks may overcome this problem through their large size and a specialized body plan that isolates highly vascularized red muscle on the dorsal surface, allowing heat to be retained near the center of the body within a massive core of white muscle. This could allow a warm-adapted species to maintain enhanced function of organs and sensory systems while exploiting food resources in deep, cool water.